Population Dynamics and Neuronal Polyploidy in the Developing Neocortex. Issue 1 (7th September 2020) - Jungas, Thomas; Joseph, Mathieu; Fawal, Mohamad-Ali; Davy, Alice
Abstract: The mammalian neocortex is composed of different subtypes of projection neurons that are generated sequentially during embryogenesis by differentiation of neural progenitors. While molecular mechanisms that control neuronal production in the developing neocortex have been extensively studied, the dynamics and absolute numbers of the different progenitor and neuronal populations are still poorly characterized. Here, we describe a medium throughput approach based on flow cytometry and well-known identity markers of cortical subpopulations to collect quantitative data over the course of mouse neocortex development. We collected a complete dataset in a physiological developmental context on two progenitor and two neuron populations, including relative proportions and absolute numbers. Our study reveals unexpected total numbers of Tbr2+ progenitors. In addition, we show that polyploid neurons are present throughout neocortex development.